Gambaran Komunikasi Efektif Dalam Penerapan Keselamatan Pasien - Fadillah Ulva (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2017)
Patient safety is one of the important issues in the hospital. Hospital was an institution that full of activity and human being. Workers, patients, visitors, and the community required the protection from health and accident. Communication influenced to medicine error as 19%. Effective communication should be a thing to be observed. In addition, effective communication is also the element of the patient safety target. The purpose of this research was to analyze the effectiveness of the communication as an effort to apply patient safety in the hospital x in Padang. The research was a qualitative study. The subject of study was 7 informant which chosen by purposive sampling. The research instruments conducting with in-depth interviews, the guidelines based on an instrument of hospital accreditation. Direct observation and review of documentation is used to support the data. The communication in X Hospital in Padang conducted orally and by telephone. A communication system used SBAR (situation, background, assessment, recommendation) and TBK (wrote, read, and confirming) do to improve the effectiveness of the communication. Effective communication is expected to reduce medical error. Communication with SBAR and TBK techniques need confirmation sheets as physical evidence. But the confirmation sheets were not yet available in X Hospital. The communication procedure to enhance effective communications in X hospital use SBAR and TBK. However the confirmation sheets were the obstacles in imply the effective communication. Suggestions that can given is the medical and nursing committee monitor and evaluate the application of effective communication.